2018
DOI: 10.1007/s00520-017-4029-5
|View full text |Cite
|
Sign up to set email alerts
|

Head and neck cancer patient experience of a new dietitian-delivered health behaviour intervention: ‘you know you have to eat to survive’

Abstract: PurposeThe aim of this study was to explore head and neck cancer (HNC) patient experiences of a novel dietitian delivered health behaviour intervention.MethodsThis study is a qualitative study which employed semi-structured individual interviews using open and axial coding and then final selective coding to organise the data. Patients with HNC who had participated in a dietitian delivered health behaviour intervention to reduce malnutrition were invited to discuss their experience of this intervention. Individ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
37
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(38 citation statements)
references
References 24 publications
1
37
0
Order By: Relevance
“…All studies reported dietary intake in accordance with estimated needs indicating high adherence. This supports the assumption that individualized dietary counselling promote adherence to dietary advices [ 40 ]. The study of Ravasco et al [ 27 ] also found that counselling resulted in a higher intake of macronutrients than just using ONS.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…All studies reported dietary intake in accordance with estimated needs indicating high adherence. This supports the assumption that individualized dietary counselling promote adherence to dietary advices [ 40 ]. The study of Ravasco et al [ 27 ] also found that counselling resulted in a higher intake of macronutrients than just using ONS.…”
Section: Discussionsupporting
confidence: 81%
“…In the present review, this approach was used in five of 11 studies with nutritional intervention [ 23 , 25 , 26 , 29 , 31 ] while one used only dietary counselling [ 28 ] and a pilot study used only ONS [ 9 ]. Dietary counselling is considered the best approach to promote adherence to dietary advices [ 39 , 40 ] since it allows an individual tailoring of the diet to personal needs and desires [ 40 , 41 ]. An indication of this was also found in one of the selected studies, designed to compare effect on dietary intake after dietary counselling, use of ONS and eating ad libitum [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…To date, one Australian study has reported on the successful delivery of a dietitian-led behavior change intervention to increase adherence to the HNC EBGs, demonstrating improvements in nutritional status, quality of life and treatment completion [ 25 , 26 , 27 ]. Few other published studies have taken a multistrategic, patient-centred approach to implementing best-practice nutrition care for patients with HNC addressing barriers and facilitators at the individual, team and system levels which are then tested in a real-world setting.…”
Section: Introductionmentioning
confidence: 99%
“…A later published study has highlighted the physical, emotional and social losses associated with decreased nutritional intake in patients with HNC (McQuestion, Fitch, & Howell, ). A recently published study explored the experiences from participating in a dietitian‐delivered health behaviour intervention during radiotherapy, by focusing on the patient's working relationship with the dietitian, specific components of the intervention and suggestions for improving the intervention (McCarter et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…A recently published study explored the experiences from participating in a dietitian-delivered health behaviour intervention during radiotherapy, by focusing on the patient's working relationship with the dietitian, specific components of the intervention and suggestions for improving the intervention (McCarter et al, 2018).…”
Section: Introductionmentioning
confidence: 99%